Desafios de jovens muçulmanos em Burquina Faso no retorno de estudo em países de língua árabe: entre vulnerabilidade e a reconstrução da cidadania - Savadogo, Pingréwaoga Béma Abdoul Hadi (2014)
Our study discuss the process of returning to homeland faced by young muslins Burkinabes who studied in countries of Arabic language Saudi Arabia, Egypt, Syria and Libya, among others. It is about a theoretical study that has been complemented with a preparatory fieldwork made at Ouagadougou (Burkina Faso), in 2010. It can be seen, by one side, the search for religious knowledge and sociocultural legitimation; by other, the problems faced at return and the role of institutions in the reconstruction of social, professional and economical network. Burkina Faso is a country taking place at west of Africa, with a population of 16.241.811 inhabitants, from which 60% are muslins. The population aged between 15 to 39 years old represents more than 31%, raising its social and economic importance. Most of the population has studied at the so called franco-arab schools, in an education imbricated with a deeply religious manner, within a context that the study of French (the official language) is a matter of secondary concern. Considering the challenges of getting a university degree, countries of Arabic speaking languages became attractive because its stronger appeal of having equivalent values and due to offers for scholarships by countries like Egypt, Syria, Libya and Saudi-Arabia. By the time of return, there are plenty of difficulties about social and professional insertion for returnees. Among the possibilities that seem to be more open there are these of teaching at Franco-Arabic schools and working for associations that promotes the Islam and rights of Islamic populations. It is noted, firstly, the social historic context of education in the country and, then, the role of Muslim Institutions, mainly, of local Islamic Universities in the process of social support in constructing spaces that aim social belonging and work.